2017
DOI: 10.1007/jhep05(2017)104
|View full text |Cite
|
Sign up to set email alerts
|

Electron and muon anomalous magnetic dipole moment in a 3–3–1 model

Abstract: We calculate, in the context of a 3-3-1 model with heavy charged leptons, constraints on some parameters of the extra particles in the model by imposing that their contributions to both the electron and muon (g − 2) factors are in agreement with experimental data up to 1σ-3σ. In order to obtain realistic results we use some of the possible solutions of the left-and right-unitary matrices that diagonalize the lepton mass matrices, giving the observed lepton masses and at the same time allowing to accommodate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 67 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…In order to fit the muon and electron g − 2 anomalies [49] we need m S ≳ 4.318 TeV and m A ≳ 4.321 TeV [50]. However, lower masses are allowed if we consider the contributions of all scalar and pseudoscalars in the model.…”
Section: Some Phenomenological Consequencesmentioning
confidence: 99%
“…In order to fit the muon and electron g − 2 anomalies [49] we need m S ≳ 4.318 TeV and m A ≳ 4.321 TeV [50]. However, lower masses are allowed if we consider the contributions of all scalar and pseudoscalars in the model.…”
Section: Some Phenomenological Consequencesmentioning
confidence: 99%
“…Therefore, it seems wise to leave these as they are until other phenomenological studies bring different constraints on the model parameters, which can give us a direction to follow among the many possibilities here presented. Some possible phenomenological studies are: the electron and muon anomalous magnetic dipole moments [14], the neutron electric dipole moment [15,16], and Flavor-Changing Neutral Currents [17]. All these observables are well suited for studies in multi-Higgs models.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that none of these models are capable of accommodating the g − 2 anomaly due to the existence of stringent collider bounds (see [87][88][89][90][91] for g − 2 studies in the context of 3-3-1 models). The masses of the gauge bosons are proportional to the energy scale at which SUð3Þ L × Uð1Þ N → SUð2Þ L × Uð1Þ Y .…”
Section: -3-1 Modelsmentioning
confidence: 99%